2012
DOI: 10.1111/j.1468-0386.2012.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

EU Constitutionalism in Flux: Is the Eurozone Crisis Precipitating Centralisation or Diffusion?

Abstract: The Lisbon Treaty was supposed to mark the end of an almost‐decade‐long period of treaty reform. After the tumult of the failed Constitutional Treaty, the settlement it imposed struck a sustainable balance between the competing forces of centralisation and the diffusion that characterise European integration. Yet this constitutional settlement is now threatened by the Eurozone debt crisis and official responses to it, most notably the proposed fiscal compact. A prevalent view regards the crisis as an opportuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Rather, the financial crisis is causing a popular backlash in both debtor and creditor countries (Scicluna, 2012). The frustration over austerity has been taken advantage of by Eurosceptic populist parties such as the NF in the European elections.…”
Section: More Danger At the Eu-levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, the financial crisis is causing a popular backlash in both debtor and creditor countries (Scicluna, 2012). The frustration over austerity has been taken advantage of by Eurosceptic populist parties such as the NF in the European elections.…”
Section: More Danger At the Eu-levelmentioning
confidence: 99%
“…This highlights "Berlin's determination for the EU to build on the Eurozone's fragile recovery from the financial crisis by creating institutions strong enough to withstand future turmoil" (Wagstyl & Barker, 2014). Despite this development, some still argue that attempts to resolve the crisis through an unrelenting faith in 'more Europe' in a political culture of total optimism,' will fail for the same reasons the Constitutional Treaty failed --any push to achieve fiscal integration will upset the balance of power drastically (Scicluna, 2012). However, The EU will have to gravitate eventually towards a banking, fiscal, and monetary union in order to prevent a perpetual financial 'doom loop ' (O'Rourke & Taylor, 2013).…”
Section: The Eurozone's Long Road To Fiscal Unitymentioning
confidence: 99%
“…Economists like Mark Blyth (2013: 156-60) and Wolfgang Streeck (2013: 48) have observed that, in the determination of economic policy, elected officials in Europe cede power to technocrats whose directives lie outside the reach of democratic accountability and, more importantly, whose understanding of economics lies on spurious intellectual foundations. From a constitutional-theoretical standpoint, and with European federalism as their common point of reference, scholars like Nicole Scicluna (2012) and Jürgen Habermas (2015) highlight the dominance of hegemonic inter-governmentalism over supranational democracy, the dominance of the European Council over the Council of Ministers and the European Parliament, and the increased role played by technocratic institutions like the ECB in European governance. Thus, across their disciplinary variations, the aforementioned studies suggest that political authority in Europe has become exceedingly concentrated in the hands of a small minority.…”
mentioning
confidence: 99%
“…It is difficult to imagine which institutional architecture might satisfy Habermas's normative ideas. 167 As…”
mentioning
confidence: 99%